Parental sociodemographics of medically assisted reproduction births in the United States: a dyadic population-level study - Ester Lazzari, Ph.D; Katherine Tierney, Ph.D (Elsevier, 2023)
Objective: To study how men's and couples' sociodemographic characteristics predict the probability of having a birth conceived using medically assisted reproduction (MAR) in the United States. Design: Population-based study. Setting: Not applicable. Patient(s): Men and women in the National Vital Statistics Birth certificate data from 2009 to 2019. Intervention: None. Main Outcome Measure(s): Proportion of MAR births out of total births by parental sociodemographic categories and probability of having a MAR birth. Result(s): Between 2009 and 2019, the overall prevalence of MAR births among men was 1.81%. Fathers of children conceived using MAR tended to be older, higher educated, and white compared with fathers of naturally conceived children. During the period of 2009-2019, these sociodemographic profiles remained largely unchanged. Controlling for maternal age and birth order only partially reduced disparities by education and race. In 2019, highly educated fathers were 2.04 percentage points (95% confidence interval, 1.97-2.12) more likely to have a MAR-conceived birth than fathers with a low educational level, and black fathers were associated with a reduction in the probability of having an MAR-conceived child by −1.07 percentage points (95% confidence interval, −1.11 to −1.04) compared with white fathers. The dyadic analysis using parents' education and race interactions revealed that partnering with someone of a higher educational level increases the likelihood of having a MAR birth, beyond what would be observed by considering only individual-level characteristics. Conclusion(s): To comprehend the environment in which MAR-conceived children are born and raised, performing dyadic analyses that examine the characteristics of both partners is essential. The findings underscore the enduring presence of substantial social disparities in MAR use in the United States, with MAR-conceived children raised in environments of relative advantage, which may impact their future health and development.